INTERNAL SUPERVISORY UNIT VOCATIONAL HIGHER EDUCATION SUPERVISION AREA OF INSPECTORATE KEMDIKBUDRISTEK - Nova Maulud Widodo; Ahmad Kudhori; Vaisal Amir (International Conference on Business Management and Accounting, 2022)
Changes organization of the KEMDIKBUDRISTEK made Polytechnic Colleges under the organization of the Director General Vocational Studies. Vocational universities were initially in the supervisory area of ​​inspector 1, now in 2022 the Vocational College is in the supervisory area ​​inspector 4. This change has also affected the communication of the internal supervisory unit at the Polytechnic with the Inspectorate General. The implementation of supervision for institutions in their business processes is the focus of the internal supervisory unit. All stakeholders are expected to be able to complete their work, even the demands for the implementation of MBKM become a challenge for the polytechnic. In the implementation of this supervision, there are adjustments to the current pandemic conditions. This study aims to determine the impact of the internal supervisory unit in vocational colleges in the area of ​​inspector supervision 4. Researchers in conducting the analysis used qualitative methods with primary and secondary data sources, while the type of data used was qualitative. Data collection methods are interviews and documentation. Furthermore, the results of data analysis were then validated for drawing conclusions. The results showed that with the return of the supervisory area of ​​vocational higher education to area 4, coordination with other universities was getting better. This result makes SPI supervision more optimal.